A Qualitative Study on Representations of Intellectual and Relational Capital Among a Group of Managers in an Italian Trade-Union - Ripamonti, Silvio Carlo; Galuppo, Laura; Petrilli, Sara; Benozzo, Angelo (Frontiers in Psychology, 2021)
The way in which managers perceive their organization's intellectual and social capital has an impact in shaping their choices and how they lead change. The aim of the study was to explore how the managers of a trade union framed the role of its intangible assets in a context of organizational change. A qualitative approach was used; 30 semi-structured interviews were conducted with the leaders of a trade union and then analyzed using the method of thematic analysis. Particular attention was paid to the metaphors the managers used to narrate change. The hypothesis underlying this approach is that metaphors are a meaningful resource in that they can convey how organization and its intangible assets are framed. In the results, three “root metaphors” are illustrated—the trade union seen either as a system of domination, an organism, or a culture—together with the consequences of each of these images for the perception and value attributed to the trade union's intangible assets. In conclusion, implications for changing management practices and for further research are discussed.